The Roles of Islamic Educational Psychology in Suppressing the Rate if Juvenile Delinquency (A Case Study of Sma Muhammadiyah Pakem Sleman and Smk Muhammadiyah Seyegan) - Zuhaery, Muhammad; Santosa, Achadi Budi (EARR (Educational Administration Research and Review), 2021)
Juvenile delinquency shows an increasing trend from year to year. It needs serious concern and immediate treatment, securing the young generation. The research is aimed to 1) identify the factors causing juvenile delinquency in SMA Muhammadiyah Pakem Sleman and SMK Muhammadiyah Seyegan Sleman, and 2) describe the Islamic educational psychology perspective in the treatment of juvenile delinquency in SMA Muhammadiyah Pakem Sleman and SMK Muhammadiyah Seyegan Sleman. The research design is descriptive with a case study approach. The data were collected through interviews and field notes. Meanwhile, the data were analyzed through organization, coding, and concluding.